Generating lineage-resolved, complete metagenome-assembled genomes from complex microbial communities - Bickhart, Derek M.; Kolmogorov, Mikhail; Tseng, Elizabeth; Portik, Daniel M.; Korobeynikov, Anton; Tolstoganov, Ivan; Uritskiy, Gherman; Liachko, Ivan; Sullivan, Shawn T.; Shin, Sung Bong; Zorea, Alvah; Andreu, Victòria Pascal; et al. (Nature biotechnology, 2022)
Microbial communities might include distinct lineages of closely related organisms that complicate metagenomic assembly and prevent the generation of complete metagenome-assembled genomes (MAGs). Here we show that deep sequencing using long (HiFi) reads combined with Hi-C binning can address this challenge even for complex microbial communities. Using existing methods, we sequenced the sheep fecal metagenome and identified 428 MAGs with more than 90% completeness, including 44 MAGs in single circular contigs. To resolve closely related strains (lineages), we developed MAGPhase, which separates lineages of related organisms by discriminating variant haplotypes across hundreds of kilobases of genomic sequence. MAGPhase identified 220 lineage-resolved MAGs in our dataset. The ability to resolve closely related microbes in complex microbial communities improves the identification of biosynthetic gene clusters and the precision of assigning mobile genetic elements to host genomes. We identified 1,400 complete and 350 partial biosynthetic gene clusters, most of which are novel, as well as 424 (298) potential host–viral (host–plasmid) associations using Hi-C data. Metagenome sequencing can now distinguish closely related microbes using long reads and haplotype phasing.